Observing animal behaviour - Dawkins, Marian Stamp (Oxford University Press, 2007)
Observing Animal Behaviour takes the reader through all these stages: from the initial observations, to the formulation of hypotheses, and their subsequent testing with further systematic observations. Although designed principally as a companion text for advanced undergraduate and students taking courses in animal behavior, this accessible text will be essential reading for anyone wanting to study animal behavior using observational methods rather than experimentation, and assumes no previous knowledge of animals, statistics or scientific method. It will be of particular relevance and use to those professional researchers and consultants in the behavioral sciences who seek a compact but comprehensive introduction to the quantitative observation of animal behavior